ISNAR on the move - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
ISNAR (International Service for National Agricultural Research) has moved its headquarters to Laan van Nieuw Oost Indie 133, 2593 BM The Hague, THE NETHERLANDS.